PROVIDÊNCIAS CABRALINAS - Araújo, Homero José Vizeu (Organon, 2012)
The cultural environment of the fifties and sixties and its effects on JoãoCabral’s poetry. The conservative modernization of the country creates the beginningsof cultural industry, which allows a secondary role for literature, despite theimportance of literature in the elite circles. Cabral’s poetry is a sophisticated reactionto this situation.